2018
DOI: 10.1111/joa.12820
|View full text |Cite
|
Sign up to set email alerts
|

The infrapatellar fat pad and the synovial membrane: an anatomo‐functional unit

Abstract: The infrapatellar pad, a fibro-adipose tissue with peculiar microscopic and mechanical features, is gaining wide attention in the field of rheumatological research. The purpose of this descriptive review is to summarize the most recent published evidence on the anatomic, physiologic and biomechanical inter-relationship between the infrapatellar fat pad and the knee synovial membrane. As an extrasynovial tissue, the infrapatellar fat pad does not directly interact with the articular cartilage; based on its loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
116
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 59 publications
0
116
0
Order By: Relevance
“…However, as of now, any article has been published on how to extract and identify exosomes in synovial tissue. Importantly, more and more researchers consider the synovial membrane and intra-articular fat pad as an anatomical unit in OA pathogenesis and pain, and inflammation of synovial membrane in the knee joint may play a central role in OA and affect not only cartilage but also intra-articular fat pad [7,29,30]. Moreover, previous team studies have shown that synovial inflammation may affect articular cartilage damage through the innate immune system, aggravating the course of OA [11].…”
Section: Discussionmentioning
confidence: 99%
“…However, as of now, any article has been published on how to extract and identify exosomes in synovial tissue. Importantly, more and more researchers consider the synovial membrane and intra-articular fat pad as an anatomical unit in OA pathogenesis and pain, and inflammation of synovial membrane in the knee joint may play a central role in OA and affect not only cartilage but also intra-articular fat pad [7,29,30]. Moreover, previous team studies have shown that synovial inflammation may affect articular cartilage damage through the innate immune system, aggravating the course of OA [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some pro-or anti-inflammatory cytokines like TNFα, IL-1β, or IFNγ, known to be secreted by synovium can induce the inflammatory response of IFP. On the other hand, it was demonstrated that, after intraarticular injection of monoiodoacetate in mice, the necrosis of adipocytes and fibrosis of the IFP are associated with synovial hyperplasia [75][76][77]. Further studies are needed to explore the adipokines and signaling pathway involved in the interaction.…”
Section: Interaction With Synoviummentioning
confidence: 99%
“…In the recent years, the potential role of the IFP in OA has been suggested by many researchers. For a long time, this peculiar extra-synovial adipose tissue was simplistically retained a deformable space filler endowed with shock absorber properties in the knee joint and a bystander in knee OA; conversely, it is now considered an emerging player in knee OA with a multifunctional role in knee joint homeostasis, also mediating joint pain and inflammation (Ioan-Facsinay and Kloppenburg, 2013;Belluzzi et al, 2017Belluzzi et al, , 2019Macchi et al, 2018). This occurs through an active secretion of cytokines and adipokines (Ioan-Facsinay and Kloppenburg, 2013) whose levels are gender dependent, being normally higher in women than in men even after adjusting for body mass index (BMI) (Poonpet and Honsawek, 2014).…”
Section: Introductionmentioning
confidence: 99%